Single and binary adsorption of Cd (II) and Zn (II) ions from aqueous solutions onto bottom ash - Hatairat Sukpreabprom (2018)
© 2014, Korean Institute of Chemical Engineers, Seoul, Korea. Bottom ash, a waste obtained from coal-burning power plant, was used as a low cost adsorbent for the removal of Cd (II) and Zn (II) ions from single and binary systems in batch experiments. The results of adsorption capacity showed that bottom ash could be considered as a potential adsorbent. The uptake of Zn (II) ion was greater than that of Cd (II) ion. For single adsorption, based on the correlation coefficient (R2) values, both Langmuir and Freundlich isotherms suitably described the adsorption equilibrium data in the initial metal ion concentration range of 10–50 mg/L. The multicomponent isotherms, including the extended Langmuir and IAST-Freundlich isotherms, were used to predict the binary adsorption of Cd (II) and Zn (II) ions. Furthermore, the appropriate multicomponent isotherm was investigated by minimizing the average relative error (ARE) function. It should be confirmed that the extended Langmuir isotherm fitted the binary adsorption equilibrium data satisfactorily.